Patriarki dalam Perspektif Pesantren - Suheri Sahputra Rangkuti (Madaniyah, 2019)
This article reviews patriarchal practices in boarding schools with sociological analysis. Islamic boarding schools as the oldest education in this country are dynamic educational institutions and continuously strive to improve themselves. But even so, the pesantren which are integrated with the local culture where it was founded still inherits a patriarchal system which could be influenced by the environment including the local culture in which the pesantren was founded. This article is here to provide a kind of sociological reasons why the patriarchal system still resides in the pesantren realm, in order to attract readers to further research.